The association between myopia and gender in Indian schoolchildren in Kuala Lumpur - Norhani Mohidin,; Saadah Mohd Akhir,; Bariah Mohd Ali,; Zainora Mohammed,; Sharanjeet K.,; Chung K.M, (penerbit ukm, 2005)
A vision screening study was carried out among Indian schoolchildren around Kuala Lumpur to determine whether the prevalence of myopia was higher in boys or girls. Altogether 749 students (49.7% boys and 50.3% girls) aged 7-18 years were screened and their refractive error examined using retinoscopy without cycloplegia. For the right eye 15.1% of the girls’ eyes were found to be myopic as compared to 16.9% of the boys, of which chi-square showed no significant difference (p = 0.44). For the left eye 18.8% of the girls’ eyes were myopic as compared to 16.4% of the boys. Chi square also showed no significant difference (p = 0.26). When high myopia (> -6.00D) was considered, there was no difference found between boys and girls. The number of students with high myopia greater than -6.00D was also very small (0.3%-0.5%). In conclusion, itwas found that there was no significant difference in myopia between girls and boys among Indian schoolchildren.